Choline Transporter Immunohistochemistry: An Effective Substitute for Acetylcholinesterase Histochemistry to Diagnose Hirschsprung Disease With Formalin-fixed Paraffin-embedded Rectal Biopsies. (July 2017) - Kapur, Raj P; Raess, Philipp W; Hwang, Samuel; Winter, Conrad
Acetylcholinesterase enzymatic histochemistry (AChE EHC), which highlights abnormal cholinergic nerves in the mucosa of aganglionic bowel, has been used for decades to evaluate rectal biopsies for Hirschsprung disease (HSCR). While useful diagnostically, AChE EHC is not compatible with conventional formalin-fixed and paraffin-embedded (FFPE) tissues and is not widely available. The choline transporter (ChT) is a putative alternative marker of cholinergic nerves. ChT immunohistochemistry (IHC) was investigated using FFPE biopsies and resections from patients with confirmed HSCR, as well as appropriate non-HSCR controls. ChT immunostaining was effective at identifying cases with HSCR and qualitatively similar to AChE EHC on frozen section. Among 3 pathologists, the diagnostic positive and negative predictive values based on ChT IHC ranged from 0.84–0.94 and 0.85–0.89, respectively, with good inter-observer agreement (Cohen kappa = 0.70–0.90). ChT IHC was useful in unusual scenarios in which calretinin (CR) IHC failed to correctly identify patients with HSCR. In 10 cases of short-segment HSCR, abnormal ChT+ mucosal innervation was present through the entire aganglionic segment and into portions of the TZ with submucosal nerve hypertrophy. In contrast, mucosal CR IHC was retained in the TZ and adjacent aganglionic bowel, which could lead to misinterpretation of a biopsy as ganglionic bowel. Indeed, 6 such patients were identified with paradoxical CR-positive mucosal innervation in their diagnostic biopsies. ChT IHC was interpreted as unequivocal HSCR in these cases, and HSCR was confirmed on resection. In summary, ChT IHC in FFPE tissue demonstrates high positive and negative predictive values for HSCR, is superior to CR IHC in a subset of cases, and can be incorporated into routine practice without the need for specialized techniques.